Mediating Effects of Digital Marketing Capability on SMEs Entrepreneurs Marketing Performance - Narakorn, Prasittichai (Creative Business and Sustainability Journal, 2020)
The objectives of this research were to study the relationship between marketing performance, platform capability, web capability and digital marketing capability of SMEs entrepreneurs in Phitsanulok Province. The multi-stage sampling survey data were collected from 315 SMEs entrepreneurs in Phitsanulok Province. Structural equation model (SEM) was analyzed using AMOS program. The results showed that our data explained the model very well whereby marketing performance was driven by platform capability, web capability and digital marketing capability. Our findings could help SMEs entrepreneurs to understand the importance of digital marketing capability which directly influences marketing performance. Particularly, those SMEs entrepreneurs with web capability should emphasize the use of website to share details of the products and the organization; and to receive customers’ suggestions and complaints. These factors are significant to the increase of the SMEs entrepreneurs’ marketing performance. The study model was conceptualized using dynamic capability theory together with digital marketing capability aiming at enhancing competitiveness of SMEs entrepreneurs in Thailand so that they can correspond to the changes of information technology and communication.